Monitoring of Heavy Metal Residues in the Meat of Some Game Birds with Insight into Their Health Risk Assessment - Mohamed, Hadeer S.; Hafez, Abd El-Salam E.; Mahmoud , Abdallah F.A. (Journal of Advanced Veterinary Research, 2023)
Due to their great nutritional value, distinct scent and taste, and lower price in contrast to other usual sources of protein, game birds' meat products are in higher demand. Toxic metals including lead (Pb), cadmium (Cd), mercury (Hg), and arsenic (As) are still present in these items, but there is a glaring lack of information on their presence. Therefore, this analysis was done to determine the residual level of lead, mercury, cadmium and arsenic were still present in three different types of game bird’s meat, including pigeons, quails and sparrows. According to the study’s findings, Pb, Cd, Hg, and As were detected at variable concentrations in the tested samples. Residual concentrations of the tested metals in several samples are over the suggested maximum permissible limits (MPL). However, Cd was low in all samples and did not exceed MPL. Furthermore, the HQ ranged from 0.04 to 0.22 for cadmium, 1.16 to 1.34 for arsenic, 0.06 to 0.07 for lead and 0.05 to 0.35 for mercury. Although HQs of studied heavy metals except for arsenic did not exceed 1, it supposedly demonstrates that eating the meat of game birds does not pose a significant health risk to people for ingesting the particular metals.